Geology : made simple - Matthews, William Henry, 1919- (Made simple books., 1983)
Geology gives a detailed study of rock-forming minerals and the rocks that are formed by it. The text analyses the forces which act on and within rocks. This subject belongs to physical geology. Historical geology is also covered in the book. This study explores the fossil content of the rock and reconstructs the earth's history over the past million years. The subjects encourage the reader to go out and examine his surroundings. First chapter of the book focuses on the description of earth. Topics such as the shape, size, and motions of the earth are discussed. The second chapter of the te.